Management of Sepsis Bundle by Nurses in Hospitals: A Scoping Review - Nurdiansyah; Yanny Trisyani; Ristina Mirwanti (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2025)
Background: Sepsis is one of the leading causes of mortality in hospitals, with a significant death rate. The management of sepsis bundles was developed by the Surviving Sepsis Campaign (SSC). Sepsis bundles include early identification, lactate measurement, antibiotic administration, and fluid resuscitation, and have been effective in reducing mortality rates. Nurses play a strategic role in implementing these bundles, as they are often the first to recognize the early signs of sepsis. However, implementation in clinical settings often faces challenges, including high workloads, limited resources, and insufficient understanding of protocols. Methods: This study used a scoping review method to explore the implementation of sepsis bundles by nurses in hospitals. Literature searches were conducted in PubMed, CINAHL/MEDLINE, Scopus, and ScienceDirect, using the following inclusion criteria: English-language articles with free full-text access and published from January 2014 to June 2024. Results: Of the 211 identified articles, 9 met the inclusion criteria and were analyzed. The findings reveal that effective implementation of sepsis bundles can improve nurses' adherence to protocols and reduce mortality rates. Factors such as continuous education, protocol revisions, leadership support, and optimal staffing policies are key to successful implementation. Conclusion: This study concludes that nurse-led sepsis bundles require a multidimensional approach to enhance clinical outcomes and operational efficiency for hospital sepsis patients.